(untitled) (Research, Society and Development, 2023)
Maytenus ilicifolia (espinheira santa) is a medicinal plant of relevant pharmacological benefit that belongs to the Celastracea family, has several therapeutic uses, the gastroprotective action being the most widespread among the population, its phytochemical composition has aroused great interest in the health area. Thus, the present study aims to address the pharmacological actions of Maytenus ilicifolia, its main clinical applications and consequences of possible interactions with other drugs. For this, an integrative bibliographic review was conducted in the databases: Scielo; VHL; Pubmed and Science Direct of articles published in the period, 2019-2022. The results reveal new in vivo research on the possible antitumor actions of Maytenus, they also report its healing, anti-inflammatory, gastroprotective, antiglycemic, antioxidant actions and make an "alert" for interactions with allopathic and/or other medication since Maytenus is Considered a competitive antagonist phytotherapeutic being contraindicated for lactating women or women who use contraceptives, its concomitant use with methotrextract, amiodarone and ketoconazole can lead to liver toxicity configuring a secondary pathology. It is concluded that, even with Maytenus presenting a positive prognosis for therapy, self-medication is still a danger to health, so that no information was found in the literature on the correct amount of infusion intake, which is the most consumed form. among plant fans, another addendum is the falsification of the species that can cause serious problems, suggesting new research on quality control, dosage and adverse effects.